PENGARUH FLEKSIBILITAS PSIKOLOGIS MELALUI ACCEPTANCE AND COMMITMENT THERAPY (ACT) TERHADAP BERBAGAI KASUS PSIKOPATOLOGIS DAN MEDIS : SEBUAH TINJAUAN PUSTAKA - Agnes Wijaya (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Abstract: Psychological flexibility is an ability to contact the present moment from moment to moment, from time to time and choose or maintain behavior that is based on values and important goals of individual life. There are six proccesses that contribute to psychological flexibility, namely present moment awareness, self as context, cognitive defusion, acceptance, chosen value, and committed to action. These six proccesses are facilitated by Acceptance and Commitment Therapy (ACT). Nine articles were selected based on inclusion and exclusion criteria in this current systematic review. Variety of atributes was examined in every research. As outcomes, effectiveness of ACT was focused on the measurement of psychological flexibility and the level of pathological symptoms on variety of psychopatological and medical cases. Results showed that ACT effectively decreased the negative aspects and increased the positive aspects of the participants on every case. The variety of cases and limitation of the researches were presented in this review. Keywords: psychological flexibility, Acceptance and Commitment Therapy, systematic review